2015
DOI: 10.3109/1354750x.2015.1068860
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 5-hydroxymethyluracil and 8-oxo-7,8-dihydroguanine as potential biomarkers in patients with colorectal cancer

Abstract: Urinary DNA modifications may reflect the oxidative stress/chronic inflammation in colorectal cancer but diagnostic performance for early-detection is moderate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Rozalski and co-workers investigated 8-oxo-7,8-dihydro-2'-deoxyguanosine, 8-oxo-7,8-dihydroguanine, and 5-hydroxymethyluracil. Group data and the main findings are reported in table 1, whereas SP and SE values are listed in table 3 71.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rozalski and co-workers investigated 8-oxo-7,8-dihydro-2'-deoxyguanosine, 8-oxo-7,8-dihydroguanine, and 5-hydroxymethyluracil. Group data and the main findings are reported in table 1, whereas SP and SE values are listed in table 3 71.…”
Section: Resultsmentioning
confidence: 99%
“…Since oxidative stress related to chronic inflammation is associated with CRC etiology, Rozalski and colleagues assessed urinary excretion of oxidatively modified DNA bases/nucleoside (8-oxo-7,8-dihydroguanine, 8-oxo-7,8-dihydro-2'-deoxyguanosine and 5-hydroxymethyluracil) in HC, adenoma patients and CRC patients 71. Although urinary DNA changes may reflect the oxidative stress/chronic inflammation found in CRC 85,86, its performance in early diagnosis is moderate 71.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of analytical techniques for measurement of urinary 8-OHdG have been developed, including enzyme-linked immunosorbent assay (ELISA)333435, capillary electrophoresis with various detectors (e.g., electrochemical or ultraviolet detection, CE-ECD or CE-UV)363738, high-performance liquid chromatography with electrochemical detection (HPLC-ECD)3940, gas chromatography-mass spectrometry (GC-MS)414243, and liquid chromatography-tandem mass spectrometry (LC-MS/MS)33344445464748495051. ELISA is the most convenient method and has received widespread use, but lack of specificity seems to be the main problem and several reports have demonstrated that ELISA frequently overestimates urinary 8-OHdG levels compared with the concentrations measured by chromatography-based techniques.…”
mentioning
confidence: 99%
“…It has been postulated that 8-oxodG is one of the sensitive biomarkers for oxidative damage of cellular DNA [13]. 8-oxodG is a useful marker for evaluating the cardiovascular risk factors and inflammatory status in hypertensive patients [14], for identifying persons at risk of developing cancer [15], for early prediction of lifestyle-related disease risk [16], and for assessing the environmental conditions that are expected to have a serious long-term impact on the health status in adults [17].…”
Section: Introductionmentioning
confidence: 99%